2020
DOI: 10.5312/wjo.v11.i10.442
|View full text |Cite
|
Sign up to set email alerts
|

Highly cross-linked versus conventional polyethylene inserts in total hip arthroplasty, a five-year Roentgen stereophotogrammetric analysis randomised controlled trial

Abstract: BACKGROUND Polyethylene (PE) particles produced by wear of the acetabular insert are thought to cause osteolysis and thereby aseptic loosening of the implant in total hip arthroplasty (THA). As highly cross-linked polyethylene (HXLPE) is presumed to give lower wear rates, in vivo studies are needed to confirm this. AIM To compare the wear of REXPOL, a HXPLE, with conventional PE within the first five years after implantation using Roentgen ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Osteolysis, attributed to polyethylene wear debris, is one of the main causes of aseptic loosening in THA (Jacobs et al 2001). Since highly cross-linked polyethylene (HXLPE) was introduced, several studies have shown reduced wear compared with ultra-high-molecular-weight polyethylene (UHMWPE), hereafter called conventional PE (Kuzyk et al 2011, van Loon et al 2020. Conventional PE liners demonstrate a mean wear rate of around 0.1 mm/year, which has been considered as the generally accepted osteolysis threshold.…”
mentioning
confidence: 99%
“…Osteolysis, attributed to polyethylene wear debris, is one of the main causes of aseptic loosening in THA (Jacobs et al 2001). Since highly cross-linked polyethylene (HXLPE) was introduced, several studies have shown reduced wear compared with ultra-high-molecular-weight polyethylene (UHMWPE), hereafter called conventional PE (Kuzyk et al 2011, van Loon et al 2020. Conventional PE liners demonstrate a mean wear rate of around 0.1 mm/year, which has been considered as the generally accepted osteolysis threshold.…”
mentioning
confidence: 99%
“…48,49 Although there is a gap in the CDA literature regarding implant design and its impact on wear, there is extensive literature in adult reconstruction supporting the use of polyethylene polymer, and the use of highly cross-linked ultrahigh molecular weight polyethylene has become the standard of care in total hip arthroplasty. 79,80 Similarly, studies on disc arthroplasty are beginning to show similar trends in wear patterns for metal-onpolymer compared with metal-on-metal designs. [50][51][52] While metal-on-metal designs can decrease the amount of wear debris, they have been associated with metal hypersensitivity and complications leading to implant failure.…”
Section: Device Failurementioning
confidence: 99%
“…The first 2 to receive Food and Drug Administration approval in 2007 were the Prestige ST, a metal-on-metal design, and ProDisc-C, a metal-on-polymer design 48,49 . Although there is a gap in the CDA literature regarding implant design and its impact on wear, there is extensive literature in adult reconstruction supporting the use of polyethylene polymer, and the use of highly cross-linked ultrahigh molecular weight polyethylene has become the standard of care in total hip arthroplasty 79,80 . Similarly, studies on disc arthroplasty are beginning to show similar trends in wear patterns for metal-on-polymer compared with metal-on-metal designs 50–52 .…”
Section: Implant Design and Wearmentioning
confidence: 99%
“…Table is modified from a study by Takanashi et al [128] Since ultrahigh-molecular-weight polyethylene (UHMWPE) used in artificial joint sliding elements wears quickly, [132][133][134][135][136][137][138][139][140][141] crosslinked UHMWPE is often used in total hip arthroplasty (THA). [142][143][144][145][146][147][148][149][150][151][152] However, crosslinked UHMWPE has low impact resistance and is hence easily breakable, with several published cases of breakage in THA. [153][154][155][156][157][158][159] For the same reason, crosslinked UHMWPE is avoided for total knee arthroplasty (TKA), which involves the convex contact of joint components.…”
Section: Nanocarbon Biomaterials Expected For Clinical Application In...mentioning
confidence: 99%